Breeding birds of Britain and Ireland - Parslow, John (Poyser Monographs., 2010)
Every one of the 887 species of birds found in Britain and Europe is described and illustrated - including all rarities and introduced species. The book provides the information needed to identify every species - whatever its age or sex - and special pages highlight groups of birds that are difficult to identify.